A lightweight hybrid encryption technique to secure IoT data transmission - Kunchok, Tenzin; Kirubanand V. B, Prof (International Journal of Engineering and Technology, 2018)
Internet of Things(IOT) is the rising innovation without bounds is required to associate billions of devices. IoT is the future where many low power resources and constrained devices are connected by means of the internet for communication, compute process and take actions in the communication network. The increased number of communication is relied upon to produce heaps of information and the security of information can be a threat resulting a secure solution for communication is necessitates among heterogenous devices. Focus of the work is to provide confidentiality, authentication and integrity of data in transit between IoT edge devices and back-end systems. This paper proposes a lightweight hybrid encryption system using ECDH key exchange mechanism for generating keys and establishing connection, digital signature for authentication, thereafter AES algorithm for encryption and decryption of user data file.Â The proposed combination is referred to as â€œthree way secured data encryption mechanismâ€ which interpret all the 3 protection schemes of authentication, info security and verification with the characteristics of lower calculation cost and faster speed makes it robust for hackers to crack the security system, thereby protective data in transmission.Â Â Â